Generalised Trust, Institutional and Political Constraints on the Executive and Deregulation of Markets - Markus Leibrecht; Hans Pitlik (Austrian Institute of Economic Research (WIFO), 2014)
It is frequently claimed that high levels of generalised trust are conducive for economic reforms. In contrast, the "traditional view" on institutional and political constraints on the executive (IPCE) postulates that high IPCE tend to paralyse the decision-making process, thus blocking required policy changes. By stressing credibility issues of economic reforms and transaction cost for special interest groups, a more positive view however sees IPCE as potentially conducive to reforms. This paper empirically explores the significance of these claims for the case of economic deregulation. In particular, it elaborates on the hypotheses that IPCE do not impact on economic reforms in an environment of high generalised trust and that the positive impact of trust increases with the extent of IPCE. The results provide evidence in favour of the traditional view on IPCE. However, it is also shown that IPCE are an obstacle for economic policy liberalisation only in relatively low trusting environments. In contrast, a robust positive correlation of generalised trust with the extent of economic deregulation is isolated, and trust unfolds a particular strength with increasing levels of IPCE.
Keywords: 330